Introduction to React - Gackenheimer, Cory (Apress : Imprint: Apress, 2015)
Introduction to React teaches you React, the JavaScript framework created by developers at Facebook, to solve the problem of building complex user interfaces in a consistent and maintainable way. React.js shrugs away common front-end conventions in an effort to make things more efficient - use Introduction to React to learn about this framework and more today. Get to know the React API and it's specific JavaScript extension, JSX, which makes authoring React components easier and maintainable. You will also learn how to test your React applications and about the tools you can use while building. Once you understand these core concepts, you can build applications with React. This will help you cement the ideas and fundamentals of React and prepare you to utilize React in your own use cas e. See how to: use React to maintain complex user interfaces in an efficient way integrate existing user interfaces and move forward with React manage application architecture using Flux easily utilize JSX, React's JavaScript extension.